2012
DOI: 10.6061/clinics/2012(10)02
|View full text |Cite
|
Sign up to set email alerts
|

A new method to analyze the subjective visual vertical in patients with bilateral vestibular dysfunction

Abstract: OBJECTIVE:The aim of this study was to assess the subjective visual vertical in patients with bilateral vestibular dysfunction and to propose a new method to analyze subjective visual vertical data in these patients.METHODS:Static subjective visual vertical tests were performed in 40 subjects split into two groups. Group A consisted of 20 healthy volunteers, and Group B consisted of 20 patients with bilateral vestibular dysfunction. Each patient performed six measurements of the subjective visual vertical test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 35 publications
0
25
0
1
Order By: Relevance
“…When compared to the arithmetic mean of SVV trials, the mean of absolute SVV values more accurately reflects the perceptual abnormalities of patients with bilateral vestibular dysfunction (Funabashi et al, 2012 ). We expected to find abnormalities in SVV given that vestibular—specifically otolithic—dysfunction is common in children with CIs (Cushing et al, 2013 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When compared to the arithmetic mean of SVV trials, the mean of absolute SVV values more accurately reflects the perceptual abnormalities of patients with bilateral vestibular dysfunction (Funabashi et al, 2012 ). We expected to find abnormalities in SVV given that vestibular—specifically otolithic—dysfunction is common in children with CIs (Cushing et al, 2013 ).…”
Section: Methodsmentioning
confidence: 99%
“…Transient abnormalities in the SVV have also been reported in adults with sudden unilateral SNHL (Ogawa et al, 2012 ). Patients with bilateral vestibular loss score similarly to control groups (Tabak et al, 1997 ; Guerraz et al, 2001 ), although a closer examination of their SVV reveals greater inter-trial variability (Funabashi et al, 2012 ). Much of the research to date has focused on visual vertical perception in adults, yet Brodsky et al ( 2016 ) have recently demonstrated that the evaluation of SVV in pediatric patients is, in fact, feasible.…”
Section: Introductionmentioning
confidence: 98%
“…It does not discriminate very well between vestibular disorders and other causes of imbalance such as cerebellar ataxia [12]. The accuracy of subjective visual vertical testing for BVH has still to be refined [162]. Many other tests can also be used in the diagnostic process if necessary: audiometry, measuring blood pressure, measuring orthostatic hypotension, blood tests (including autoantibodies, complement factors, folate, vitamin B 12 , renal function, thyroid function, glucose, genetics, etc.…”
Section: Challenges In Establishing a Diagnosis Of Bvhmentioning
confidence: 99%
“…La sensibilidad de la prueba del balde es de 89% si se evalúa monocularmente o 90% si es binocular, de repetirse la prueba 10 veces la sensibilidad aumenta a 92% para detectar alteraciones utriculares periféricas 12 . SVV ha sido utilizado ampliamente para estudiar alteraciones del equilibrio, en diversos contextos, con gran impacto en la toma de decisiones y manejo de pacientes [24][25][26][27][28][29][30][31][32] .…”
Section: Introductionunclassified